THU0525 Safety of adalimumab ± methotrexate for the treatment of polyarticular juvenile idiopathic arthritis (PJIA): strive registry. (15th June 2017) - Ruperto, N; Brunner, H; Nanda, K; Toth, M; Foeldvari, I; Bohnsack, J; Milojevic, D; Rabinovich, C; Kingsbury, D; Marzan, K; Quartier, P; Minden, K; et al.
Abstract : Background: JIA is the most common chronic inflammatory rheumatic disease of childhood. TNF inhibitors are used for long-term control of pJIA disease. Objectives: To evaluate the 7 year (y) safety of Adalimumab treatment with or without methotrexate (ADA±MTX) when used in current clinical practice for treatment of patients (pts) with active pJIA. Methods: This is a 7 y interim analysis of an ongoing, multicenter, non-interventional, observational registry of pts with pJIA with up to10 y safety follow-up. Included pts were treated with ADA±MTX or MTX alone as comparison arm according to routine clinical care in PRINTO/PRCSG centres in EU, USA and Australia. MedDRA observational adverse events (AEs) were recorded from 1st day in the registry through last contact, irrespective of duration of registry treatment. Results: In January 2014, enrollment was complete. As of June 1, 2016 cut-off date, 838 pts (301- MTX arm and 537 - ADA±MTX arm) were treated in the registry. There were 39 pts who rolled over from MTX to ADA±MTX arm. At registry entry mean pJIA disease duration was 1.3 y and 3.7 y and mean AJC71 was 5.8 and 5.2 for MTX and ADA±MTX arms, respectively. CHAQ disability index was 0.6 for both arms. Mean duration of study drug exposure in registry was 2.0 y (range: 0.0 – 7.1) and 2.5 y (range: 0.0 – 7.9) for MTX and ADA±MTX arms, respectively. Mean duration of observation in registry was 3.9 y (range: 0.0 – 7.2) and 3.5 y (range: 0.0 – 7.9) for MTX and ADA±MTX arms, respectively. Overall, 213 pts (70.8%) in MTX and 225 pts (41.9%) in ADA±MTX arms discontinued registry drug through 7 y. Main reasons (not exclusively) for registry drug discontinuation for MTX arm: pts required additional therapy (32.6%), other (13.3%), lack of efficacy (11.6%), AEs (9.3%), or pts achieved JIA remission (8.6%); for ADA±MTX arm: lack of efficacy (17.9%), other (7.3%), lost to follow-up (5.6%), AEs (5.4%), or pts achieved JIA remission (5.0%). Frequencies and rates of treatment-emergent AEs (from 1st dose date of registry drug in registry up to last dose + 70 days in registry, excluding AEs occurring during treatment interruption) were similar to those reported for observational AEs (from 1st day in registry up to last contact irrespective of drug treatment duration) (Table). Rate of serious infections was similar between MTX and ADA±MTX arms. One pt (0.2%) reported an event of opportunistic infection (fungal oesophagitis) in ADA±MTX arm. No reports of deaths, malignancies, active tuberculosis, oral candidiasis, demyelination, or congestive heart failure. Conclusions: Overall, ADA±MTX was well-tolerated in these pts with pJIA with no new safety signals. The retention rate for registry drug was higher in ADA±MTX arm compared to MTX arm. Acknowledgements: AbbVie sponsored the study & contributed with PRINTO & PRCSG to analysis, review, approval of the abstract. X. Leahy & A. Deshmukh (AbbVie) contributed to research. Medical writing: G. Patki (AbbVie). Disclosure of Interest: N. Ruperto Grant/research support from: AbbVie Inc., AstraZeneca, Bristol-Myers Squibb, Janssen Biologics B.V., Eli Lilly and Co., "Francesco Angelini", GlaxoSmithKline, Italfarmaco, Novartis, Pfizer, Roche, Sanofi Aventis, Schwarz Biosciences GmbH, Xoma, and Wyeth Pharmaceuticals, Employee of: GASLINI Hospital, Speakers bureau: Astellas, AstraZeneca, Bristol-Myers Squibb, Italfarmaco, Janssen Biologics B.V., MedImmune, Roche, and Wyeth/Pfizer, H. Brunner Consultant for: AbbVie Inc., AstraZeneca, Centocor, Bristol-Myers Squibb, Boehringer-Ingelheim, Pfizer, Regeneron, Hoffman La-Roche, Novartis, Takeda, UCB, and Genentech, Speakers bureau: Genentech Pharmaceuticals, K. Nanda Consultant for: Medac Pharma, Inc., M. Toth: None declared, I. Foeldvari Consultant for: AbbVie and Novartis, J. Bohnsack Consultant for: Novartis, D. Milojevic Consultant for: Genentech and Novartis, C. Rabinovich Grant/research support from: UCB Pharma, Janssen, D. Kingsbury: None declared, K. Marzan Grant/research support from: AbbVie, P. Quartier Grant/research support from: AbbVie, Novartis, Pfizer, BMS, Chugai-Roche, Medimmune, Servier, and Swedish Orphan Biovitrum, Consultant for: AbbVie, Novartis, Pfizer, BMS, Chugai-Roche, Medimmune, Servier, Swedish Orphan Biovitrum, and Sanofi, K. Minden Grant/research support from: Pfizer, AbbVie and Roche/Chugai, Consultant for: Pfizer, Roche, and Pharma-Allergan, Speakers bureau: Pfizer, Roche, and Pharma-Allergan, E. Chalom Speakers bureau: AbbVie, G. Horneff Grant/research support from: AbbVie, Pfizer, Novartis, and Roche, Speakers bureau: AbbVie, Novartis, Sobi, Pfizer, and Roche, R. Kuester Grant/research support from: AbbVie Inc. and Wyeth/Pfizer, J. Dare Grant/research support from: AbbVie, AstraZeneca, Bristol-Myers Squibb, Horizon Pharma, Medac, Pfizer, Roche, and UCB, M. Bereswill Shareholder of: AbbVie, Employee of: AbbVie, J. Kalabic Shareholder of: AbbVie, Employee of: AbbVie, H. Kupper Shareholder of: AbbVie, Employee of: AbbVie, A. Martini Grant/research support from: AbbVie Inc., AstraZeneca, Bristol-Myers Squibb, Janssen Biologics B.V., Eli Lilly and Co., "Francesco Angelini", GlaxoSmithKline, Italfarmaco, Novartis, Pfizer, Roche, Sanofi Aventis, Schwarz Biosciences GmbH, Xoma, and Wyeth Pharmaceuticals, Employee of: GASLINI Hospital, Speakers bureau: Astellas, AstraZeneca, Bristol-Myers Squibb, Italfarmaco, and MedImmune, D. Lovell Consultant for: AstraZeneca, Centocor, Bristol-Myers Squibb, Pfizer, Regeneron, Hoffman La-Roche, Novartis, UBC, Xoma, Genentech, Amgen and Forest Research, Speakers bureau: Wyeth Pharmaceuticals